Arnold Schönberg's Verklärte Nacht [music] : transcription for two pianos - Magalhaes, Luis Miguel de Araujo; Schoenberg, Arnold,1874-1951. Verklärte Nacht; arr (Stellenbosch : University of Stellenbosch, 2012)
Thesis (M. Mus.) -- University of Stellenbosch, 2002.